Communication community detection algorithm based on ranking of strength - Hong-quan WEI; Hong-chang CHEN; Li-xiong LIU; Ju-long LAN (Tongxin xuebao)
According to the characteristics of how to effectively describe real weighted network of the current telecom network problems,improvement and development of related models of complex networks,especially for communication community detection results hierarchy was not clear and the problem of high complexity,from the analysis of the characteristics of complex network,a new algorithm for community detection design communication.The algorithm to achieve effective communication strength ranking method based on community detection in communication,communication density distribution of generating high resolution based on hierarchical nesting tree,the distance vector pruning nested tree,the level of analysis and structure of community stability and reduce the computational complexity.The algorithm is verified using real network data.